2013
DOI: 10.5194/hess-17-1783-2013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of predictions in ungauged basins – Part 1: Runoff-hydrograph studies

Abstract: Abstract. The objective of this assessment is to compare studies predicting runoff hydrographs in ungauged catchments. The aim is to learn from the differences and similarities between catchments in different locations, and to interpret the differences in performance in terms of the underlying climate and landscape controls. The assessment is performed at two levels. The Level 1 assessment is a metaanalysis of 34 studies reported in the literature involving 3874 catchments. The Level 2 assessment consists of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
187
2

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(201 citation statements)
references
References 61 publications
12
187
2
Order By: Relevance
“…The findings of the present study do not support the results of previous studies that reported better performance of the nearest neighbor than the physical similarity (e.g. Merz and Blöschl, 2004;Parajka et al, 2005;Oudin et al, 2008;Zhang and Chiew, 2009;Parajka et al, 2013).…”
Section: Regional Performancecontrasting
confidence: 56%
See 3 more Smart Citations
“…The findings of the present study do not support the results of previous studies that reported better performance of the nearest neighbor than the physical similarity (e.g. Merz and Blöschl, 2004;Parajka et al, 2005;Oudin et al, 2008;Zhang and Chiew, 2009;Parajka et al, 2013).…”
Section: Regional Performancecontrasting
confidence: 56%
“…Parajka et al (2013) categorized parameter regionalization methods into five groups. The first method is based on regional calibration by utilizing data from multi-sites in the region.…”
Section: Regionalization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of conceptual modeling, regionalization of parameters for ungauged watersheds were categorized by three approaches (Peel and Blöschl, 2011): (a) regression analysis between individual parameters and watershed properties (e.g., Kim and Kaluarachchi, 2008;Gibbs et al, 2012); (b) parameter transfer based on spatial proximity (e.g., Vandewiele et al, 1991;Oudin et al, 2008); and (c) physical similarity (e.g., McIntyre et al, 2005;Oudin et al, 2008Oudin et al, , 2010. Even if the performance of these three approaches was dependent on climatic conditions, performance and complexity of the model, and other factors, several studies concluded that the spatial proximity method was attractive due to its better performance and simplicity (Oudin et al, 2008;Parajka et al, 2013). Hence, this study used the proximity-based regionalization for regulated watersheds.…”
Section: Regionalizationmentioning
confidence: 99%